Mapping global acceptance and uptake of COVID-19 vaccination: A systematic review and meta-analysis - Qian Wang; Simeng Hu; Fanxing Du; Shujie Zang; Yuting Xing; Zhiqiang Qu; Xu Zhang; Leesa Lin; Zhiyuan Hou (Communications Medicine, 2022)
Wang, Hu et al. provide a systematic review and meta-analysis on global acceptance and uptake of COVID-19 vaccination. Lower vaccine acceptance is seen in females, Black people, and those with lower income.